Discourse Markers In A Vlog Video By BNay Channel - Cahyanti, Rika (Language Horizon: Journal of Language Studies, 2021)
English learning process of EFL learners is often evaluated through their performance in using the language, especially their speaking performance. This research concern about the use of discourse markers in informal occasion which may be a great help to improve speaking fluency of EFL. This research revealed the types and functions of discourse markers used in vlog video by BNay Channel. To conduct this research, the researcher relied on Biber et al (1999) theory in classifying the types of discourse markers and Castro (2009) theory for defining the function of the discourse markers. To get the data, the researcher applied qualitative approach. From this research, the writer found ten types of discourse markers applied by the speakers in their speech. After further analyzing the data, the writer found that the discourse markers used by the speaker served both textual and interpersonal functions divided into several sub-functions. This research showed that the dominant function of discourse markers shown in the data is response or reaction markers and back-channel signals which helps the speaker express a response or reaction to the previous discourse including back-channel signals of understanding and continued attention while other speaker is having his/her turn.